Delivery of neurotrophic factors in the treatment of age-related chronic neurodegenerative diseases. (3rd March 2020) - Padmakumar, Smrithi; Taha, Maie S.; Kadakia, Ekta; Bleier, Benjamin S.; Amiji, Mansoor M.
ABSTRACT: Introduction: Neurodegenerative diseases are those wherein the neurons in the brain or peripheral nervous system lose their function, eventually culminating in neuronal death. Aging acts as the predominant factor here due to the reduced protein turnover rate in aging cells. As neurotrophic factors possess imperative roles in protecting the neurons and restoring their functionality, design of different modalities to deliver them to the brain would significantly enhance the therapeutic benefits. Areas covered: This review covers the various mechanisms of neurodegeneration, its molecular link with aging, different neurotrophic factor classes and their potentials, current treatment strategies, the challenges associated with the delivery of neurotrophic factors, administration routes, design of different delivery vehicle design, alternative modalities of delivery, and the clinical translational challenges of these strategies. Expert opinion: A deeper molecular level understanding about the complexity of neurodegeneration, discovery of potential biomarkers, which helps identifying the right targets, finding the accurate animal model completely recapitulating the human scenario, and a validated design of clinical trials would immensely help in overcoming the present challenges. The substantial developments in the field of gene therapy, usage of small molecules and peptide mimetics, combinatory approaches, etc. definitely give brighter hopes.